(3JMbjb GdfUQI aj JdNjU eYGde OGQ GdgLQIs - (3CHh HcQ (B((3YHO Gddg(B) (3Hf GdMSjf Hf YeQ, CHh eMeO GdeUQj GdTGaYqj GdeQGZj GdbQTj, Rjf GdOjf,J (B816 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdeOjfI GdTQjaI OGQ gLQI QShdg s
(3BNQgG (B:s
(3JeJ hHJeGegG Je cJGH GdJMbjb s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B60s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B84 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B378s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs